PELA COMPLETA RESSOCIALIZAÇÃO DO AGRESSOR E POR UMA MAIOR VALORIZAÇÃO DA VÍTIMA: O USO DA JUSTIÇA RESTAURATIVA NOS CASOS DE VIOLÊNCIA DOMÉSTICA - León, Andrea Catalina; Mascarenhas, Fabiana; Stellet, Gabriela Sepúlveda; Genovez, Juliane dos Santos; Sales, Juneflower Franco (Revista da AJURIS - Qualis A2, 2012)
FOR THE FULL RE-SOCIALIZATION OF THE AGGRESSOR AND REHABILITATION OF THE VICTIM: THE USE OF RESTORATIVE JUSTICE IN CASES OF DOMESTIC VIOLENCE RESUMO: A presente pesquisa, a partir da revisão bibliográfica e teórica das literaturas nacional e estrangeira sobre o tema da justiça restaurativa, da análise de decisões judiciais, relatos de pessoas envolvidas em casos de violência doméstica e dos debates legislativo-jurisprudenciais sobre a limitação imposta pela Lei Maria da Penha ao uso de instrumentos processuais conciliatórios, objetiva demonstrar que o instituto da justiça restaurativa é uma alternativa capaz de trazer resultados eficientes nos casos de violência doméstica contra as mulheres. Tendo em vista que, ao contrário da lógica adversarial estabelecida pelo processo judicial, o cerne da justiça restaurativa está em restabelecer o diálogo entre os envolvidos, onde o mediador é apenas um facilitador, não tendo posição de comando, a justiça restaurativa possibilita um verdadeiro acesso à justiça, direito constitucional que não restringe à judicialização das lides, pois tem como escopo o alcance da justiça em seu significado essencial. Mediante o estabelecimento de critérios que confiram senso às medidas estabelecidas em cada caso, segundo as necessidades e os interesses das partes envolvidas, e sem deixar de lado a perspectiva de gênero, o processo judiciário passa a constituir uma oportunidade transformadora. Assim, evidencia-se que um enfoque restaurativo, e não só punitivo, está mais perto da transformação real dos padrões socioculturais que naturalizam a violência contra as mulheres cotidianamente, em contraposição à política criminal de intervenção punitiva estatal que impede o surgimento de mudanças reais nas normas sociais. PALAVRAS-CHAVE: Violência doméstica; justiça restaurativa; mediação. ABSTRACT: Based on bibliographical and theorical revision of the national and foreign juridical literature about the subject of Restorative Justice, as well as analysis of judicial decisions, reports of people involved in cases of domestic violence against women and jurisprudential-legislative debates about the limits imposed by Maria da Penha Law on the use of legal conciliatory instruments, this study aims to demonstrate that the institute of Restorative Justice is able to bring effective results in cases of domestic violence against women. Moreover, it dialogues with the Latin American context, especially in Colombia, looking to see this issue under the comparative viewpoint. Given that, in opposition to the adversarial logic established by judicial process, the core of the Restorative Justice is about reestablishing the dialogue between stakeholders, where the mediator is only a facilitator that doesn’t takes the position of command, the Restorative Justice enables the real access to Justice, which is a constitutional right that’s not restrict the judicialization of the controversy, as it has as scope the extent of the Justice in its essential meaning. Through the establishment of criterions that give sense to the measures set in each case according to the needs and interests of the involved persons, and without leaving aside the perspective of the genus, the judicial process becomes to provide an opportunity for transformation. Thus, it is evident that a restorative approach, not just punitive, is closer to the real turn of the socio-cultural pattern that naturalize the violence against women daily, in opposition to the criminal politics of state punitive intervention, which prevents the emerging of real changes in social norms. Aiming to enrich these reflections, this work incorporates elements of the experience of supporting women in situations of domestic violence in Colombia, through their own perspectives about the meaning of appealing to the judicial system, as well as from observations attested in specific cases in regards to the functioning of the Legal System. KEYWORDS: Domestic violence; restorative justice; interposition. SUMÁRIO: Introdução; 1 A violência doméstica deve ser punida; 2 É possível recompor o lar abalado pela agressão?; Considerações finais; Referências. SUMMARY: Introduction; 1 The domestic violence must be punished; 2 Is it possible to restore the home environment affected by the aggression?; Final considerations; References.